Protein profiles of bronchoalveolar lavage fluid from patients with pulmonary sarcoidosis - Kriegova, Eva; Melle, Christian; Kolek, Vitezslav; Hutyrova, Beata; Mrazek, Frantisek; Bleul, Annett; du Bois, Roland M; von Eggeling, Ferdinand; Petrek, Martin (American journal of respiratory and critical care medicine, 2006)
BACKGROUND: Pulmonary sarcoidosis is a multisystem granulomatous disease with various clinical phenotypes. So far, there has been little information on protein patterns (PPs) of bronchoalveolar lavage fluid (BALF) from patients with sarcoidosis and no data are available on PPs in clinical disease subtypes. OBJECTIVES: To investigate the PP of BALF from patients with pulmonary sarcoidosis, to evaluate whether PPs reflect disease course as assessed by chest X-ray (CXR), and to compare PPs between patients with/without Löfgren's syndrome. METHODS: Surface-enhanced laser desorption/ionization-time-of-flight mass spectroscopy was applied to investigate PPs in unconcentrated BALF from 65 patients (CXR stage I, n = 32; CXR stage II, n = 22, CXR stage III, n = 11) and 23 healthy control subjects. The Mann-Whitney U test was used to detect differentially expressed protein peaks. After reversed-phase fractionation, peptide fingerprint mapping and immunodepletion were used to identify deregulated (up-regulated or down-regulated) proteins. RESULTS: Forty differentially expressed protein entities (2.75-185.62 kD) were detected in patients with pulmonary sarcoidosis versus control subjects (p < 0.05). Whereas 13 peaks (33%) were present across all CXR stages, 27 (67%) were specific for particular CXR stages. Comparison of PPs between CXR stage I patients with or without Löfgren's syndrome revealed 25 differentially expressed peaks. The total number of deregulated peaks and also of those associated with sarcoidosis as a whole were markedly lower in patients with Löfgren's syndrome in comparison with other sarcoid phenotypes. Human serum albumin, alpha1-antitrypsin, and protocadherin-2 precursor were identified from sarcoidosis-associated PP. CONCLUSION: Surface-enhanced laser desorption/ionization-time-of-flight mass spectroscopy enables determination of protein patterns in sarcoid BALF and allows detection of protein patterns linked to a particular disease course.
Keywords: senioři; respirační funkční testy; Up-Regulation; stupeň závažnosti nemoci; Disease Progression; Statistics, Nonparametric; Male; alveolární makrofágy; upregulace; progrese nemoci; proteiny; Sarcoidosis, Pulmonary; plicní sarkoidóza; down regulace; Middle Aged; Sensitivity and Specificity; mužské pohlaví; Probability; Spectrometry, Mass, Matrix-Assisted Laser Desorption-Ionization; studie případů a kontrol; pravděpodobnost; Macrophages, Alveolar; peptidové mapování; Adult; Peptide Mapping; neparametrická statistika; bronchoalveolární lavážní tekutina; Down-Regulation; čipová analýza proteinů; ženské pohlaví; referenční hodnoty; Protein Array Analysis; Humans; Reference Values; biologické markery; Respiratory Function Tests; Bronchoalveolar Lavage Fluid; lidé středního věku; senzitivita a specificita; spektrometrie hmotnostní - ionizace laserem za účasti matrice; dospělí; Biomarkers; Female; Aged; Severity of Illness Index; Proteins; lidé; Case-Control Studies